Multidisciplinary insights from new AIB fellows - Boddewyn, J. J. (Emerald, 2014)
Each year, the Fellows of the Academy of International Business (AIB) spot and elect new talents to join them and expand research in international business. Only 21 Fellows were elected between 2008 and 2012. Ten of them have contributed chapters to this volume, the first of two of which will feature unique insights from the AIB's best and brightest. Each chapter addresses the important questions facing researchers today and answers them in three distinct cultural, theoretical, and managerial contexts.
Includes index.
Keywords: International business enterprises -- Management.; International business enterprises -- Social aspects.; elektronické knihy; electronic books